Light-mediated multi-target protein degradation using arylazopyrazole photoswitchable PROTACs (AP-PROTACs). Issue 78 (6th September 2022) - Zhang, Qisi; Kounde, Cyrille S.; Mondal, Milon; Greenfield, Jake L.; Baker, Jennifer R.; Kotelnikov, Sergei; Ignatov, Mikhail; Tinworth, Christopher P.; Zhang, Leran; Conole, Daniel; De Vita, Elena; Kozakov, Dima; et al.
Abstract : A new class of arylazopyrazole photoswitchable PROTACs (AP-PROTACs) enables light-triggered degradation of a specific ensemble of protein kinases. Abstract : Light-activable spatiotemporal control of PROTAC-induced protein degradation was achieved with novel arylazopyrazole photoswitchable PROTACs (AP-PROTACs). The use of a promiscuous kinase inhibitor in the design enables this unique photoswitchable PROTAC to selectively degrade four protein kinases together with on/off optical control using different wavelengths of light.